Level of Physical Fitness International Standard School Pilot Students at SMPN 8 Padang and SMPN 1 Rantau Pandan - Jasman, Endri; Bahdi, Masrial; Kibadra, Kibadra (Jurnal Guru Peneliti Professional, 2018)
Based on the symptoms of the level of physical fitness of the International Standard School Pilot Project (RSBI), SMPN 8 Padang is better than SMPN 1 Rantau Pandan, Bungo Regency, so the problem is the difference in the level of physical fitness. This study aims to determine the differences in the level of physical fitness of RSBI students at SMPN 8 Padang and SMPN 1 Rantau Pandan, Bungo Regency. This study is an espost facto, to determine differences in the level of physical fitness, the population of this study were 304 students of class VIII RSBI SMPN 8 Padang and SMPN 1 Rantau Pandan, Bungo Regency, with the sampling technique used was purposive sampling, namely the sampling represented by each VIII grade male student school. A as many as 52 people. The tool used for data collection was a physical fitness test, then analyzed by descriptive method. To determine the difference test is done by using the "t" test. The results revealed that there was a difference in the Physical Fitness Level of Students at the RSBI 8 Padang State Senior High School in comparison to the Physical Fitness Level of the Students at SMPN 1 Rantau Pandan in Bungo Regency. This was proven by the results of the research that tcount = 3.31> ttable = 2.20. This means that Ha is accepted while Ho is rejected. Where the Physical Fitness Level of Students at the RSBI SMPN 8 Padang is better than the Physical Fitness Level of Students at SMPN 1 Rantau Pandan, Bungo Regency.